Tourism Destination Management (Case Study in Department of Culture and Tourism Pasuruan Regency) - Putra, Sony Manggala; Wijaya, Andy Fefta; Nurpratiwi, Ratih (Graduate School, Universitas Brawijaya, 2015)
The tourism sector as one of the leading sectors in Pasuruan still faces many obstacles. The constraints associated with conditions that require improvement on tourist destination related to the presence of infrastructure, zoning, the gap between the tourism destination in the West and the East area, up to the level of visitation which has decreased from year to year. The aims of the studi were to describe and analyze Tourism Destination Management conducted by Department of Culture and Tourism Pasuruan at Banyu Biru and Ranu Grati object to become competitive and sustainable tourism destination. This study used a qualitative approach with a case study method locus in the Department of Culture and Tourism Pasuruan. The results of this study indicate that the tourism destination management of Banyu Biru and Ranu Grati when reviewed in terms of competitiveness, still needs a lot of improvement related to the presence of tourism facilities and the quality of employees as service providers. In terms of sustainability, it shows that the synergy between the regional government and tourism stakeholders need to be improved. The need for the establishment of cooperation with third parties in management of tourism destination in Banyu Biru and Ranu Grati, can be used to optimize the carrying capacity and tourist destination marketing system at Banyu Biru and Ranu Grati in order to compete in a competitive and sustainable way Keywords: tourism destination management, competitiveness, sustainability